2006
DOI: 10.1007/s10652-005-5664-9
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Venturi Principle to Water Aeration Systems

Abstract: The concentration of dissolved oxygen is an important indicator of water quality because aquatic life lives on the dissolved oxygen in the water. Aeration can increase dissolved oxygen when levels become deficient. Hydraulic structures can significantly improve dissolved oxygen levels by creating turbulent conditions where small air bubbles are carried into the bulk of the flow. Recent researches have focused on developing measurement and predictive techniques for oxygen transfer at hydraulic structures to mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 20 publications
0
35
0
3
Order By: Relevance
“…Bubbles can be produced by cavitation, initiated by hydrodynamic means, ultrasound, a laser or particle beam [10], or by direct dispersion of the gas in a liquid with different diffusers, usually made from porous materials [11], with gas flow through a submerged nozzle or orifice [12][13][14], in swirling jet flow [15], a Venturi nozzle [16], etc. An excellent state-of-theart review of different schemes and devices for small-bubble generation and their applications can be found in a recent paper [17].…”
Section: Introductionmentioning
confidence: 99%
“…Bubbles can be produced by cavitation, initiated by hydrodynamic means, ultrasound, a laser or particle beam [10], or by direct dispersion of the gas in a liquid with different diffusers, usually made from porous materials [11], with gas flow through a submerged nozzle or orifice [12][13][14], in swirling jet flow [15], a Venturi nozzle [16], etc. An excellent state-of-theart review of different schemes and devices for small-bubble generation and their applications can be found in a recent paper [17].…”
Section: Introductionmentioning
confidence: 99%
“…This reduces the possibility of caustic chemicals being sprayed into the air through cracks or breaks in the pipe. Recently, Baylar and Emiroglu [1], Emiroglu and Baylar [2], Baylar et al [3], Baylar and Ozkan [4], Ozkan et al [5] and Baylar et al [6,7] studied the use of venturi tubes in water aeration systems. All of these works were experimental and none concentrated specifically on Computational Fluid Dynamics (CFD) modeling of venturi tubes.…”
Section: Introductionmentioning
confidence: 99%
“…He and Bai [9] found that the k-ε model was in agreement with experimental data on wet gas flow in the Venturi meter. Due to the water quality improvement caused by aeration, by using a Venturi flow with holes, the aeration coefficient relationship was examined and found to be well within the geometrical parameters experimentally and numerically [10][11][12].…”
Section: Introductionmentioning
confidence: 92%